Modellbasierte Wirkkettenanalyse zur Bewertung technischer Änderungen - Wiechel, Dominik
Der unsystematische und ineffiziente Umgang mit technischen Änderungen führt zuhohen Personalkosten durch Mehraufwand, einer reduzierten Entscheidungsqualität und kannin Projektfehlschlägen resultieren. Herausforderungen beim Umgang mit technischen Änderungenliegen in der Berücksichtigung relevanter Ursache-Wirkungs-Zusammenhänge, der quantitativen und qualitativen Bewertung der Auswirkungen und der effizienten prozessualen Einbindung. Mithilfe eines modellbasierten Lösungsansatzes lassen sich die Auswirkungen technischer Änderungen schneller bewerten und fundierte Entwicklungsentscheidungen treffen. In der vorliegenden Dissertation wird eine Methodik für die Entwicklung modell-basierter Wirkkettenanalysen zur Bewertung technischer Änderungen beschrieben. Durch die modellbasierte Wirkkettenanalyse können direkt oder indirekt von der Änderung betroffene Modellelemente identifiziert werden. Das Datenmodell wird mithilfe von Abfragesprachen analysiert und die Auswirkungen werden mithilfe von integrierten Metriken quantifiziert. Die Ergebnisse der Wirkkettenanalyse werden in rollenspezifischen Sichten bereitgestellt, wodurch eine bedarfsgerechte Entscheidungsunterstützung gewährleistet wird. Die Validierung anhand von vier industriellen Fallstudien belegt die Praxistauglichkeit der Methodik. Die Methodik verbindet das Änderungsmanagement mit den Vorteilen einer modellbasierten Systementwicklung und bildet somit einen synergetischen neuen Forschungsbereich.

Effekte nachhaltigkeitsbezogener Kontexte beim Chemielernen - Wittkopp, Laura; Pollmeier, Pascal; Fechner, Sabine (Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik e.V. (GDCP))

Second order optimality conditions in a new Lagrangian formulation for optimal control problems - Konopik, Michael; Leyendecker, Sigrid; Maslovskaya, Sofya; Sina Ober-Blöbaum, Sina Ober-Blöbaum; Almagro, Rodrigo T. Sato Martín de (arXiv:2507.06024)
It has been shown recently that optimal control problems with the dynamical constraint given by a second order system admit a regular Lagrangian formulation. This implies that the optimality conditions can be obtained in a new form based on the variational approach. In this paper we extend the first order necessary optimality conditions obtained previously to second order optimality conditions. This results in a complete characterization of the optimality conditions in a new Lagrangian form.

Variational integrators for a new Lagrangian approach to control affine systems with a quadratic Lagrange term - Konopik, Michael; T. Sato Martín de Almagro, Rodrigo; Maslovskaya, Sofya; Ober-Blöbaum, Sina; Leyendecker, Sigrid (Journal of Nonlinear Science)

A new Lagrangian approach to optimal control of second-order systems - Konopik, Michael; Leyendecker, Sigrid; Maslovskaya, Sofya; Ober-Blöbaum, Sina; T. Sato Martín de Almagro, Rodrigo (Nonlinearity)

Ultrabright, two-color photon pair source based on thin-film lithium niobate for bridging visible and telecom wavelengths - Babel, Silia; Bollmers, Laura; Roeder, Franz; Ridder, Werner; Golla, Christian; Köthemann, Ronja; Reineke, Bernhard; Herrmann, Harald; Brecht, Benjamin; Eigner, Christof; Padberg, Laura; Silberhorn, Christine (Optics Express)
We present the design and characterization of a guided-wave, bright, and highly frequency non-degenerate parametric down-conversion (PDC) source in thin-film lithium niobate. The source generates photon pairs with wavelengths of 815 nm and 1550 nm, linking the visible wavelength regime with telecommunication wavelengths. We confirm the high quality of the generated single photons by determining a value for the heralded second-order correlation function as low as g_h^(2)=(6.7+/-1.1)*10^8-3). Furthermore, we achieve a high spectral brightness of 0.44·10pairs/(smWGHz) which is two orders of magnitude higher than sources based on weakly guiding waveguides. The shape of the PDC spectrum and the strong agreement between the effective and nominal bandwidth highlight our high fabrication quality of periodically poled waveguides. The good agreement between the measured and simulated spectral characteristics of our source demonstrates our excellent understanding of the PDC process. Our result is a valuable step towards practical and scalable quantum communication networks as well as photonic quantum computing.

Segmented finger electrodes to optimize ultra-long continuous wafer-scale periodic poling in thin-film lithium niobate - Bollmers, Laura; Spiegelberg, Noah; Rüsing, Michael; Eigner, Christof; Padberg, Laura; Silberhorn, Christine (Nanophotonics)
Periodically poled thin-film lithium niobate (TFLN) crystals are the fundamental building block for highly-efficient quantum light sources and frequency converters. The efficiency of these devices is strongly dependent on the interaction length between the light and the nonlinear material, scaling quadratically with this parameter. Nevertheless, the fabrication of long, continuously poled areas in TFLN remains challenging, the length of continuously poled areas rarely exceeds 10 mm. In this work, we demonstrate a significant progress in this field achieving the periodic poling of continuous poled areas of 70 mm length with a 3 μm poling period and a close to 50 % duty cycle. We compare two poling electrode design approaches to fabricate long, continuous poled areas. The first approach involves the poling of a single, continuous 70 mm long electrode. The second utilize a segmented approach including the poling of more than 20 individual sections forming together a 70 mm long poling area with no stitching errors. While the continuous electrode allows for faster fabrication, the segmented approach allows to individually optimize the poling resulting in less duty cycle variation. A detailed analysis of the periodic poling results reveals that the results of both are consistent with previously reported poling outcomes for shorter devices. Thus, we demonstrate wafer-scale periodic poling exceeding chiplet-size without any loss in the periodic poling quality. Our work presents a key step towards highly-efficient, narrow-bandwidth and low-pump power nonlinear optical devices.

Eine Demokratie, die das Recht der Frauen nicht verwirklicht, ist nichtig". Das politische Meisterstücke der Olympe de Gouges (1748-1793) - Hagengruber, Ruth Edith (ZDPE)

LLMs For Warm and Cold Next-Item Recommendation: A Comparative Study across Zero-Shot Prompting, In-Context Learning and Fine-Tuning - Halimeh, Haya; Freese, Florian; Müller, Oliver (International Conference on Information Systems Development)
Recommendation systems are essential for delivering personalized content across e-commerce and streaming services. However, traditional methods often fail in cold-start scenarios where new items lack prior interactions. Recent advances in large language models (LLMs) offer a promising alternative. In this paper, we adopt the retrieve-and-recommend framework and propose to fine-tune the LLM jointly on warm-and cold-start next-item recommendation tasks, thus, mitigating the need for separate models for both item types. We computationally compare zero-shot prompting, in-context learning, and fine-tuning using the same LLM backbone, and benchmark them against strong PLM-based baselines. Our findings provide practical insights into the trade-offs between accuracy and computational cost of these methods for next-item recommendation. To enhance reproducibility, we release the source code under https://github. com/HayaHalimeh/LLMs-For-Next-Item-Recommendation.git.

Preserving Sovereignty and Privacy for Personalization: Designing a Federated Recommendation System for Data Spaces - Halimeh, Haya; zur Heiden, Philipp (2025 27th International Conference on Business Informatics (CBI))
Data spaces have become a strategic pillar of Europe's digital agenda, enabling sovereign, legally compliant data sharing within decentralized ecosystems. As data space initiatives evolve, personalized recommendations are increasingly recognized as key use cases. However, traditional recommendation approaches typically rely on centralized aggregation of user behavior data-directly conflicting with the core ethos of data spaces: sovereignty, privacy, and trust. Federated recommendation systems offer a promising alternative by training models locally and exchanging only intermediate parameters to build a global model. Despite this potential, the integration of federated recommendation techniques and data space architectures remains largely underexplored in research and practice. This paper addresses this gap by designing and evaluating a prototype of a federated recommendation system specifically tailored for data spaces and compliant with their underlying infrastructure. Our findings highlight the viability of developing privacy-preserving, collaborative recommendation systems within data spaces, and contribute to the broader adoption of AI across these emerging ecosystems.

Towards Greener Choices: Decision Information Nudging for Sustainability-Aware Recommender Explanations - Halimeh, Haya; Müller, Oliver
Recommender systems (RS) can support sustainable development by steering users toward more sustainable choices. Sustainability-aware explanations represent one avenue for contributing to this goal by foregrounding the environmental and social aspects of the recommended products or services. This paper advances the line of research on sustainability-aware explanations by integrating nudging mechanisms into their design and by evaluating their effectiveness through a randomized between-subjects online vignette experiment across two item domains (). Our findings offer actionable design guidelines for building RS that foster sustainability-aware decision making and enrich the empirical foundation for impact-oriented research on explanation in RS.

Positionspapier Use Case 1: Vernetzte Kulturplattformen - Althaus, Maike; Beverungen, Daniel; Flath, Beate; Halimeh, Haya; Hansmeier, Philipp; zur Heiden, Philipp; Kundisch, Dennis; Müller, Michelle; Müller, Oliver; Oberthür, Simon; Vorbohle, Christian; Momen Pour Tafreshi, Maryam; et al.

Dynamic Wind Tunnel Testing of an INDI-Based Flight Controller for a Tiltrotor-VTOL - Henkenjohann, Mark; Nolte, Udo; Jahneke, Julien; Reimer, Oliver; Abrams, Stefan; Sion, Fabian; Henke, Christian; Trächtler, Ansgar; Schubert, Sebastian; Pfifer, Harald (AIAA SCITECH 2025 Forum)

Development of a Learning-Based Control System for Robot-Assisted Grinding of Rubber Roller - Reiling, Fabian; Bause, Maximilian; Gröger, Stefan; Henke, Christian; Koppert, Steven; Trächtler, Ansgar (2025 11th International Conference on Automation, Robotics, and Applications (ICARA))

Oxidation‐Enhanced Piezocatalytic Activity in Carbon Nitride‐Based Catalysts for Hydrogen and Hydrogen Peroxide Production - Pan, Ying; Liao, Luocheng; Zhang, Xinwen; Liu, Yunya; Su, Ran; Lopez Salas, Nieves (ChemSusChem)
Driven by the urgent need for a green, safe, and cost‐effective approach to producing H 2 and H 2 O 2 —both highly valuable in green energy and environmental protection fields—piezocatalysis, which converts mechanical energy into valuable chemicals, has emerged as a promising solution. However, current catalyst systems face challenges due to the need for materials with both a strong piezoelectric effect and favorable catalytic activity. Herein, the construction of an oxidized carbon nitride ( g ‐C 3 N 4 ) matrix anchored with TiO 2 nanoparticles via alkaline hydrothermal treatment is reported. Under ultrasonication, the g ‐C 3 N 4 /TiO 2 composite exhibits optimal performance under carefully controlled alkaline hydrothermal conditions. With a low concentration of Ba(OH) 2 during hydrothermal treatment, Ba(OH) 2 provides an alkaline medium, oxidizing the g ‐C 3 N 4 species and introducing structural defects into the g ‐C 3 N 4 framework. The disruption of the g ‐C 3 N 4 matrix, along with its interaction with TiO 2 nanoparticles, enhances the piezoelectric effect. Consequently, the oxidized g ‐C 3 N 4 /TiO 2 composite achieves a remarkable H 2 production rate of 4427.2 μmol g −1 and an H 2 O 2 production rate of 809.3 μmol g −1 within 1 h without the addition of any sacrificial agents or cocatalysts. This work presents an effective strategy for the structural optimization of g ‐C 3 N 4 ‐based materials and may inspire new approaches for designing advanced piezocatalysts.

Engineering Charge Polarized Au Sites for Low‐Temperature Acetylene Hydrochlorination - Li, Chun; Liu, Ruoting; Zhang, Zilong; Zuo, Fangmin; Jiang, Tingting; Zhang, Haifeng; Wang, Bolin; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Abstract Cationic gold catalyzed acetylene hydrochlorination represents a classical landmark in eliminating global mercury pollution, but their sustainable implementation is hindered by acetylene‐dependence design criteria and high operating temperatures. Herein, a platform of carbon‐supported single‐atoms Au catalysts (Au/BC and Au/NC) with polarized charge characteristics are developed via engineering Au sites with hosted B, N configurations. The negatively charged Au/BC catalyst unlocks the low‐temperature inactivity (413–423K) of the Au/NC catalyst while exhibiting superior catalytic performance in the 433–473K operating temperature range. We confirm that the classical scaling relationships on acetylene can be broken by narrowing the adsorption capacity between acetylene and HCl on Au δ⁻ sites via facilitating the back‐donation of d electrons into the antibonding orbitals of acetylene. Prolonging the durability of Au catalysts is achieved through preceding an additional robust Au δ⁻ → Au δ⁺ cycle prior to the classic Au δ⁺ → Au 0 route. This work opens a promising avenue for low temperature vinyl chloride production.

Adenine and D‐Ribose Coderived Activated Carbon with N‐Methyl‐2‐Pyrrolidone‐Modified Aqueous Electrolyte for Long‐Life Zinc‐Ion Capacitors - Tao, Li; Li, Chun; Lu, Xuejun; Mir, Rameez Ahmad; Lopez Salas, Nieves; Liu, Jian (Batteries & Supercaps)
Aqueous zinc (Zn)‐ion capacitors (AZICs) have addressed considerable attention due to their high energy density, low toxicity, and rich abundance of Zn metal. However, the development of ultra‐long cycle life and high energy density AZICs is often hindered by the lack of adequately optimized active carbon (AC) electrodes and compatible electrolytes. Herein, high‐performance, free‐standing AC electrodes for AZICs are derived from sustainable precursors—adenine and D‐ribose—using magnesium chloride hexahydrate as an activation agent via a eutectic template strategy. Furthermore, an aqueous hybrid electrolyte tailored to the designed AC electrodes is developed, significantly enhancing the stability and cycle life of AZICs. The resulting AZIC achieves a high specific capacity of 164.39 F g −1 at 0.1 A g −1 and a magnificently long cell life of over 50 000 cycles with nearly 94.5% capacitance retention at 10 000 th cycles, and 76.3% at 50 000 th cycle. The pouch cell assembly also demonstrates comparable specific capacitance and energy density to the coin cell, underscoring the potential of large‐scale applications of AZICs.

Interfacial engineering of CuSe2/FeSe2 heterojunctions for water splitting: a pathway to high-performance hydrogen and oxygen evolution reactions - Kumari, Sandhyawasini; Pahra, Swapna; Tripathy, Amrita; Sumanth, N.; Lopez Salas, Nieves; Tiwari, Santosh K.; Khan, Afaq Ahmad; Devi, Pooja; Santosh, M. S. (Nanoscale)
Enhanced bifunctional electrocatalysis via CuSe 2 /FeSe 2 heterojunctions for efficient water splitting was achieved.

Heteroatom co-doped green pea peel-derived biochar for high-performance energy storage applications - Makinde, Wasiu Olakunle; Hassan, Mohsen A.; Semida, Wael M.; Pan, Ying; Guan, Guoqing; Lopez Salas, Nieves; Khalil, Ahmed S. G. (RSC Advances)
Green pea peel (GPP) is a waste, and it is abundant and available to be used for biochar synthesis.

Enhancing NiS performance: Na-doping for advanced photocatalytic and electrocatalytic applications - Dileepkumar, V. G.; Pahra, Swapna; Lopez Salas, Nieves; Basavaraja, B. M.; Khan, Afaq Ahmad; Sumanth, N.; Devi, Pooja; Santosh, M. S. (Nanoscale)
Alkali metal doping is a new and promising approach to enhance the photo/electrocatalytic activity of NiS-based catalyst systems.